2012
DOI: 10.1371/journal.pone.0041916
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of the Western Regional Research Center Brachypodium T-DNA Insertional Mutant Collection

Abstract: The model grass Brachypodium distachyon (Brachypodium) is an excellent system for studying the basic biology underlying traits relevant to the use of grasses as food, forage and energy crops. To add to the growing collection of Brachypodium resources available to plant scientists, we further optimized our Agrobacterium tumefaciens-mediated high-efficiency transformation method and generated 8,491 Brachypodium T-DNA lines. We used inverse PCR to sequence the DNA flanking the insertion sites in the mutants. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 60 publications
1
102
0
Order By: Relevance
“…leaf) or in nonlignified tissue (endosperm). This coexpression study (Supplemental Table S3) revealed that both laccases are coexpressed with genes involved in monolignol biosynthesis, such as O-methyltransferase (Bradi3g16530; Bragg et al, 2012;Dalmais et al, 2013), cinnamoyl-CoA reductase (Bradi3g36887), or Phe ammonia lyase (Bradi3g49250 and Bradi3g49260). They are also coexpressed with three cellulose synthase genes specific to the secondary cell wall, CESA4 (Bradi3g28350), CESA7 (Bradi4g30540), and CESA8 (Bradi2g49912; Handakumbura et al, 2013).…”
Section: Bdlac5 and Bdlac6 Are Mainly Expressed In Lignified Tissuesmentioning
confidence: 96%
“…leaf) or in nonlignified tissue (endosperm). This coexpression study (Supplemental Table S3) revealed that both laccases are coexpressed with genes involved in monolignol biosynthesis, such as O-methyltransferase (Bradi3g16530; Bragg et al, 2012;Dalmais et al, 2013), cinnamoyl-CoA reductase (Bradi3g36887), or Phe ammonia lyase (Bradi3g49250 and Bradi3g49260). They are also coexpressed with three cellulose synthase genes specific to the secondary cell wall, CESA4 (Bradi3g28350), CESA7 (Bradi4g30540), and CESA8 (Bradi2g49912; Handakumbura et al, 2013).…”
Section: Bdlac5 and Bdlac6 Are Mainly Expressed In Lignified Tissuesmentioning
confidence: 96%
“…Its fully sequenced genome is highly syntenic to the genomes of important monocot crops such as wheat, rice, barley, millet, and maize, thus allowing functional and comparative genomic studies with potential for direct translation to field crops (International Brachypodium Initiative, 2010). Many genomic and functional resources have been developed around Brachypodium, including microarrays, yeast two-hybrid libraries, ;200 inbred accessions, EMS/TILLING lines, and annotated T-DNA knockout lines (Filiz et al, 2009;Fox et al, 2010;International Brachypodium Initiative, 2010;Brkljacic et al, 2011;Cao et al, 2011;Bragg et al, 2012). Brachypodium has become an accepted model plant for research related to plant-pathogen interactions, as evidenced by the growing list of publications (Routledge et al, 2004;Parker et al, 2008;Peraldi et al, 2011;Cui et al, 2012;Lee et al, 2012;Mandadi and Scholthof, 2012).…”
Section: Monocot Antiviral Responses: a Knowledge Gapmentioning
confidence: 99%
“…A substantial collection of brachypodium T-DNA mutants has been created (Thole et al, 2010;Bragg et al, 2012), and efforts are underway to develop homozygous lines for insertions in or near genes. Since publication of the initial description of the WRRC brachypodium T-DNA collection (Bragg et al, 2012), the resource has expanded to contain approx. 22 000 mutants from which >25 000 insertion sites have been identified (http://brachypodium.pw.usda.gov/TDNA/).…”
Section: Mutant Resources For the Study Of Plant-pathogen Interactionmentioning
confidence: 99%
“…However, genomic brachypodium resources are rapidly accumulating (Brkljacic et al, 2011); key resources include a sizable collection of T-DNA mutants (Bragg et al, 2012) and a publicly available TILLING resource (Dalmais et al, 2013), as noted above. Increasingly powerful sequencing technologies are facilitating high-throughput characterization of mutant collections (Polko et al, 2012) and rapid identification of causal mutations within TILLING populations (Nordstrom et al, 2013).…”
Section: Future Prospects For Brachypodium As a Model For Cereal-pathmentioning
confidence: 99%